Entropy and the City. GHG Emissions Inventory: a Common Baseline for the Design of Urban and Industrial Ecologies - Pezzagno, Michele; Rosini, Marco (TeMA - Journal of Land Use, Mobility and Environment, 2014)
From a thermodynamic point of view, the attribution of the adjective sustainable to an open system like the city is, at least, very problematic. The biosphere is a closed system, kept far from the thermodynamic equilibrium by the flow of energy coming from the sun. The biosphere maintains and increases its internal order dispersing entropy, generated by all the internal processes, as thermal infrared radiation. But then, the elegant picture of sustainability given by thermodynamics can not be applied to open systems, and notably to the city, without raising both theoretical and practical problems. The city is almost by definition a place of consumption and of degradation of potentials, kept in local equilibrium by external flows of matter and energy, but at the same time plays a key role in shaping and maintaining the global flows of matter, energy, and information, and this role must be taken into account when interpreting thermodynamic-based descriptions. The urban capital probably represents the greatest investment made by mankind. Materials have been harvested from the earth crust and from the natural systems, and have been concentrated and ordered in the city. But the "city" is not the infrastructure: it’s concept of a different logical type. The city is a further level of organization that produces services of higher level. The urban infrastructure is necessary, but not sufficient to produce the city services. The city is the most important social and health "device". A proper accounting must consider the city-performance of the urban infrastructure, beyond the mere, local energy and carbon efficiency. In this context, local GHG accounting is proposed as a rather simple and useful basis to ground process-wise studies and projects, including the creation of effective local industrial ecologies, in a continuous city-making effort toward higher sustainability.